Cybersecurity of the information space of a higher education institution - Lukashevych, Serhii; Palkova, Karina (Archives of Criminology and Forensic Sciences, 2024)
The article examines the impact of cybercrime on the work of higher education institutions and the ways to prevent and overcome cyberattacks. It is substantiated that the use of computer technology, along with its benefits, poses certain threats in terms of the complexity of data protection. It is found that today the global trends in countering cyber threats are inferior to the attackers, which leads to aggressive and successful cyber attacks by the latter. It is proved that attacks on learning networks have recently intensified significantly. Organisational measures to address cybersecurity issues are proposed. Based on the material studied, it is concluded that the effectiveness of countering cyber attacks and, as a result, the successful and stable functioning of higher education institutions in Ukraine depends on the level of preparedness, competence and responsibility of the participants.